30.4k views
3 votes
6x+3y=24 y=-2x+8 plz help

2 Answers

3 votes

Answer:

No Solution

Explanation:

6x+3y=24....equation(1)

y=-2x+8....equation(2)

put equn(2) into equn(1)

6x+3(-2x+8)=24

combine the bracket and 3

6x-6x+24=24

combine the like terms

6x-6x=24-24

0=0

No Solution

User Sebs
by
4.9k points
4 votes

Solve for the first variable in one of the equations, then substitute the result into the other equation.

Point Form:

(x,−2x+8)(x,-2x+8)

Equation Form:x=xy=−2x+8



User Sagan
by
5.0k points